2005
DOI: 10.1143/jjap.44.4350
|View full text |Cite
|
Sign up to set email alerts
|

(Bi1/2Na1/2)TiO3-(Bi1/2K1/2)TiO3-BaTiO3-Based Lead-Free Piezoelectric Ceramics

Abstract: The piezoelectric properties of lead-free x(Bi1/2Na1/2)TiO3-y(Bi1/2K1/2)TiO3-zBaTiO3 [BNBKy:z(x); y:z = 4:1 and 2:1, x+y+z=1] with tetragonal compositions were investigated, focusing on the secondary phase transition T 2 from the ferroelectric to antiferroelectric phases. Although the T 2 temperatures of BNBK near the MPB composition remained at about 115°C, T 2 rapidly shifted to a higher temperature of 200°C or higher for the off-MPB composition [x≤0.75 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
52
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 14 publications
3
52
1
Order By: Relevance
“…Promising lead-free ferroelectrics (FEs) include compositions based on sodium potassium niobate Na (1Àx) K x NbO 3 (KNN) and bismuth sodium titanate Bi 1/2 Na 1/2 TiO 3 (BNT). [3][4][5][6][7][8] In 2007, Zhang et al 9 reported a new pseudo-ternary composition, replacing a small fraction of BNT with KNN from the Bi 1/2 Na 1/2 TiO 3 -BaTiO 3 (BNT-BT) system, which showed large electric-field-induced strain values (0.45% at 8 kV/mm). This field-induced strain response remains stable against temperature 10 and cyclic fatigue.…”
mentioning
confidence: 99%
“…Promising lead-free ferroelectrics (FEs) include compositions based on sodium potassium niobate Na (1Àx) K x NbO 3 (KNN) and bismuth sodium titanate Bi 1/2 Na 1/2 TiO 3 (BNT). [3][4][5][6][7][8] In 2007, Zhang et al 9 reported a new pseudo-ternary composition, replacing a small fraction of BNT with KNN from the Bi 1/2 Na 1/2 TiO 3 -BaTiO 3 (BNT-BT) system, which showed large electric-field-induced strain values (0.45% at 8 kV/mm). This field-induced strain response remains stable against temperature 10 and cyclic fatigue.…”
mentioning
confidence: 99%
“…Interestingly, the temperature for FE-to-AFE transition has been assigned to T d instead of T s in the later publications. [19][20][21][22] In fact, the use of T d for FE-to-AFE transition is conceptually more logical than that of T s in that the FE-to-AFE transition in this type of materials is supposed to be a first-order transition 12 and consequently should be frequency-independent with a sharp peak in the corresponding dielectric responses. It is, however, noted that T d is always lower than T s , 23 which makes the deviation from the structural data in the literature even larger.…”
mentioning
confidence: 99%
“…Promising lead-free piezoelectrics are mainly based on solid solutions incorporating either Bi 1/2 Na 1/2 TiO 3 (BNT) or Na x K 1-x NbO 3 (KNN). [2][3][4][5][6][7] Although lead-free compositions of piezoelectric materials have been reported with excellent properties, no single composition has been identified with the potential for the replacement of PZT over the range of technological application conditions. To further improve the electro-mechanical properties of these materials, a comprehensive understanding of the underlying microscopic origin of the electric-field-induced strain is requisite.…”
mentioning
confidence: 99%